A case of transcatheter prosthetic aortic valve endocarditis - Muhammad Shabbir Rawala; Amna Saleem Ahmed; Syed Bilal Rizvi; Aravinda Nanjundappa (Greater Baltimore Medical Center, 2020)
Transcatheter aortic valve implantation (TAVR) constitutes an established treatment in inoperable or high perioperative risk patients with severe aortic stenosis. Prosthetic valve endocarditis after ΤΑVR occurs with an incidence of 0.3-1% per patient-year. Infective endocarditis may stem from hematogenous dissemination or contact with infected adherent tissue. Few cases of infective endocarditis after TAVR have been reported. We present an interesting case of a 79-year-old male with a history of severe aortic stenosis status post TAVR greater than one year ago, and pulmonary vein isolation for atrial fibrillation six weeks ago was found to have infective endocarditis with a vegetation on the prosthetic valve leading to multiple embolic strokes as a result of Enterococcus faecalis bacteremia. The patient was not a surgical candidate with his Society of Thoracic Surgery (STS) risk score being 18%; therefore, he was managed conservatively on intravenous antibiotics. Our case had endocarditis from enterococcus bacteremia; however, the patient never had any gastrointestinal or genitourinary procedure.